The Economic Value Added in Hotel Business by Components of the System Approach - V. PANTELEIEV (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
Based on a critical review of novel material, the content of the value-based approach with the implementation of economic value added (EVA) in the hotel activities is demonstrated; the sources of its accounting and information support are outlined; effective practices of EVA in market economies are analyzed; principles of the system approach in using EVA in hotel business (goal, entry in the system, transformation process, external environment, exit from the system and feedback) are outlined; proposals on management of enterprises engaged in hotel business, which will be appropriate for Ukraine, are formulated. A critical review of research material taken from scientific publications and hotel operation practices allowed for analysis and substantiation of improvements in the hotel business of Ukraine using EVA with reliance on the system approach.  International experiences of EVA use in the hotel business are considered for finding solutions to problems existing in Ukraine.